2019
DOI: 10.1111/cas.14109
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry for identification of CCND1, NSD2, and MAF gene rearrangements in plasma cell myeloma

Abstract: The t(11;14)/CCND1‐IGH, t(4;14)/NSD2(MMSET)‐IGH, and t(14;16)/IGH‐MAF gene rearrangements detected by fluorescence in situ hybridization (FISH) are used for risk stratification in patients with multiple myeloma (MM). Compared with conventional FISH techniques using fresh cells, immunohistochemistry (IHC) is much more cost‐ and time‐efficient, and can be readily applied to routinely prepared formalin‐fixed, paraffin‐embedded (FFPE) materials. In this study, we performed tissue FISH and IHC employing FFPE specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that some genetic mutations are closely related to the poor outcome of MM, including chromosomal alterations t (4; 14), t (14; 16), and t (14; 20). Due to chromosomal translocation, oncogenes such as MMSET/FGFR3, CCND3, CCND1, MAF, and MAFB are still regulated by the IgH gene enhancer and their expressions increase (11, 32). As a result, the cyclin D family members are upregulated, leading to the dysregulation of the G1/S checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that some genetic mutations are closely related to the poor outcome of MM, including chromosomal alterations t (4; 14), t (14; 16), and t (14; 20). Due to chromosomal translocation, oncogenes such as MMSET/FGFR3, CCND3, CCND1, MAF, and MAFB are still regulated by the IgH gene enhancer and their expressions increase (11, 32). As a result, the cyclin D family members are upregulated, leading to the dysregulation of the G1/S checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The t(4;14)(p16;q32) translocation results in deregulation of the histone methyltransferase MMSET (also known as WHSC1/ NSD2/KMT3G) [29,30], which causes an increase in the H3K36me2 level and a decrease in the H3K27me3 level in the entire genome, resulting in derangement of transcriptional programs including cyclin D2 overexpression [31,32]. The translocations t(14;16)(q32;q23) and t(14;20)(q32;q11) up-regulate Maf family transcription factors c-Maf and MafB, the target genes of which also include cyclin D2 [33]. On the other hand, the precise mechanism by which hyperdiploidy transforms plasma cells is not yet understood; however, the most prevalent (~ 30%) hyperdiploid aberration, trisomy 11, may cause cyclin D1 overexpression due to an increase in gene dosage.…”
Section: Molecular Events At the Initiation Of Myelomagenesismentioning
confidence: 99%